Genome-wide analysis of N(1)-methyl-adenosine modification in human tRNAs - Saikia, Mridusmita (Cold Spring Harbor Laboratory Press, 2010)
The N(1)-methyl-Adenosine (m(1)A58) modification at the conserved nucleotide 58 in the TΨC loop is present in most eukaryotic tRNAs. In yeast, m(1)A58 modification is essential for viability because it is required for the stability of the initiator-tRNA(Met). However, m(1)A58 modification is not required for the stability of several other tRNAs in yeast. This differential m(1)A58 response for different tRNA species raises the question of whether some tRNAs are hypomodified at A58 in normal cells, and how hypomodification at A58 may affect the stability and function of tRNA. Here, we apply a genomic approach to determine the presence of m(1)A58 hypomodified tRNAs in human cell lines and show how A58 hypomodification affects stability and involvement of tRNAs in translation. Our microarray-based method detects the presence of m(1)A58 hypomodified tRNA species on the basis of their permissiveness in primer extension. Among five human cell lines examined, approximately one-quarter of all tRNA species are hypomodified in varying amounts, and the pattern of the hypomodified tRNAs is quite similar. In all cases, no hypomodified initiator-tRNA(Met) is detected, consistent with the requirement of this modification in stabilizing this tRNA in human cells. siRNA knockdown of either subunit of the m(1)A58-methyltransferase results in a slow-growth phenotype, and a marked increase in the amount of m(1)A58 hypomodified tRNAs. Most m(1)A58 hypomodified tRNAs can associate with polysomes in varying extents. Our results show a distinct pattern for m(1)A58 hypomodification in human tRNAs, and are consistent with the notion that this modification fine tunes tRNA functions in different contexts.